Dinamika Kesetaraan Gender: Perjuangan Perempuan Aceh Dalam Olahraga Sepak bola di Tengah Norma Sosial dan Adat Istiadat - Mahmudin Aritanoga; Agung Cahyadi; Masyitah; Tawakal (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to understand the role of social institutions such as families, schools, sports organizations, and local governments in supporting or hindering women's participation in sports. The research method uses a qualitative descriptive approach that is exploratory and the implementation of research in Bireuen district, Aceh province. The research subjects involved 27 informants from several community institutions, government and non-government institutions. Such as athletes and former women's soccer athletes, then officials/coaches/referees of Askab PSSI Bireuen, Bireuen community leaders who have been involved in soccer, traditional leaders (Aceh Customary Council) Bireuen, MPU (Ulama Consultative Assembly) Bireuen, DISPORAPAR Bireuen, and KONI Bireuen. Data collection techniques were carried out with semi-structured interviews (in-depth interviews), participant observation, and documentation. Based on data identification and analysis, these findings reveal that: Shows a consistent pattern in all informant groups that recognizes women's participation space but with conditions (sharia clothing and having a special field). Then, parental support is very strong and athletes are motivated by high-achieving athletes, while support from Askab PSSI, the government, and the community is still limited. Furthermore, it confirms that the fatwa on women's football that was issued in 2019 by the Aceh MPU was never officially issued, but was only a personal opinion from the Deputy MPU Aceh at that time which was then widely circulated in the community's interpretation as an MPU Aceh fatwa. Conclusion, This study reveals that Acehnese women's participation in football takes place in a space full of social, cultural, and religious negotiations.